Synthesis of gymnoascolide A - Baag, Md. Merajuddin; N. P. Argade (Synthesis-Stuttgart, 2008)
Recently isolated 4-benzyl-3-phenylfuran-2,5-dione and antifungal gymnoascolide A have been synthesized using the chemoselective S(N)2' coupling of phenylmagnesium bromide with dimethyl 2-(bromomethyl)fumarate, chemoselective allylic substitution of bromide in 3-(bromomethyl)-4-phenylfuran-2,5-dione with phenylmagnesium bromide and regioselective N-Selectride-induced reduction of 3-benzyl-4-phenylfuran-2,5-dione as the key reactions.
Keywords: dimethyl (bromomethyl)fumarate; functionalized maleic anhydrides; gymnoascolide A; regioselective reduction; S(N)2 ` Grignard coupling reaction